2018
DOI: 10.1080/15402002.2018.1545651
|View full text |Cite
|
Sign up to set email alerts
|

Coping Processes, Self-Efficacy, and CPAP Use in Adults With Obstructive Sleep Apnea

Abstract: Background:Coping strategies are predictive of 1-week CPAP use. Coping strategies may predict longer-term CPAP use among adults with obstructive sleep apnea (OSA). Objectives:To investigate the influence of two coping styles (active and passive) and individual coping processes on CPAP use at 1-week and 1-month; and explore the association between selfefficacy and coping on CPAP use.Participants: CPAP-naïve adults (52.3% male, 90.9% white) newly diagnosed with OSA (AHI ≥ 5 events/hour) from two U.S. clinical sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…Therefore, it is more important to choose the appropriate treatment pressure. Titration is critical to the compliance and efficacy of patients with subsequent CPAP therapy [ 21 ]. At present, the CPAP technology itself has made many improvements including the diversification of ventilation modes, pipe heating, and humidification, as well as the closure and comfort of the mask, but the degree of improvement in patient compliance is still limited.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, it is more important to choose the appropriate treatment pressure. Titration is critical to the compliance and efficacy of patients with subsequent CPAP therapy [ 21 ]. At present, the CPAP technology itself has made many improvements including the diversification of ventilation modes, pipe heating, and humidification, as well as the closure and comfort of the mask, but the degree of improvement in patient compliance is still limited.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, parents or caregivers may assist children to solve with some CPAP issues such as mask leakage. 24 BPAP, non-invasive ventilation, is more comfort than CPAP resulting in better adherence. 25 A previous study showed that BPAP had significantly used hours/night than CPAP (2.72 vs 1.49 hours, P < .001) in OSA patients with poor adherence to CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…Selfefficacy can affect the treatment process either positively or negatively. For this reason, looking at the self-efficacy levels of the patients while planning the treatment will make it easier to reach the goal (Saconi et al, 2020;Topcu & Oguz, 2017). The preparation of the appropriate care plan will contribute positively to the process of the disease and the power of the individual to manage the process.…”
Section: What Does This Paper Contribute To the Wider Global Clinical Community?mentioning
confidence: 99%
“…Another study investigating the relationship between the problem-focused coping and self-efficacy in patients with stroke found a strong relationship (Tielemans et al, 2015). Studies investigating the relationship between the use of problem-focused and emotion-focused coping strategies, self-efficacy and the use of Continuous Positive Airway Pressure (CPAP) in adults with obstructive sleep apnoea found that those with higher self-efficacy and who used problem-focused coping strategies had a higher rate of CPAP use and thus a higher rate of compliance with the treatment (Saconi et al, 2020). Individuals with high self-efficacy expend more effort and a longer amount of time than those with low self-efficacy against possible adverse conditions, and they continue their efforts to achieve their goals using more effective coping strategies in any adverse condition (Ozdemir & Tasci, 2013).…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation